DESI Mg ii Absorbers: Extinction Characteristics and Quasar Redshift Accuracy - Lucas Napolitano; Adam D. Myers; Victoria A. Fawcett; Jessica Aguilar; Steven Ahlen; Davide Bianchi; David Brooks; Todd Claybaugh; Shaun Cole; Axel de la Macorra; Biprateep Dey; Andreu Font-Ribera; et al. (The Astronomical Journal)
In this paper, we study how absorption-line systems affect the spectra and redshifts of quasi-stellar objects (QSOs), using catalogs of Mg ii absorbers from the early data release and first data release of the Dark Energy Spectroscopic Instrument. We determine the reddening effect of an absorption system by fitting an unreddened template spectrum to a sample of 50,674 QSO spectra that contain Mg ii absorbers. We find that reddening caused by intervening absorbers ( v _off  >  3500 km s ^−1 ) has an average color excess of $\overline{E(B-V)}$ = 0.04 mag. We find that the E ( B − V ) tends to be greater for absorbers at low redshifts, or those having Mg ii absorption lines with higher equivalent widths, but shows no clear trend with v _off for intervening systems. However, the $\overline{E(B-V)}$ of associated absorbers, those at v _off  <  3500 km s ^−1 , shows a strong trend with v _off , increasing rapidly with decreasing v _off and peaking (∼0.15 mag) around v _off  = 0 km s ^−1 . We demonstrate that Mg ii absorbers impact redshift estimation for QSOs by investigating the distributions of v _off for associated absorbers. We find that at z  > 1.5, these distributions broaden and bifurcate in a nonphysical manner. In an effort to mitigate this effect, we mask pixels associated with the Mg ii absorption lines and recalculate the QSO redshifts. We find that we can recover v _off populations in better agreement with those for z  < 1.5 absorbers and in doing so typically shift background QSO redshifts by Δ z  ≈ ± 0.005.